Comprehensive Handbook of Psychopathology - Sutker, Patricia B.; Adams, Henry E. (Springer US, 2002)
The purpose of this handbook, originally published in 1984, was to provide a compreh- sive review of current clinical descriptions, research , and theories of psychopathology. Descriptive psychopathology is a ?eld that forms the foundation of clinical practice and research in clinical psychology, psychiatry, psychiatric social work, psychiatric nursing, and allied professions in mental health. Since the 1st edition, the editors have devised and updated a handbook to cover both general and speci?c topics in psychopathology that would be useful to researchers, practitioners, and graduate or other advanced students in the mental health and behavioral medicine professions. To implement this plan, we have very carefully chosen colleagues whom we respect for their expertise in particular ?elds. These authors include both clinicians and researchers who have outstanding national reputations, as well as more junior behavioral scientists and clinicians who, in our opinion, will achieve similar recognition in the future. The excellent chapters in this book lead us to believe that we have chosen wisely. We would like to express our appreciation to these authors for their outstanding contributions and cooperation.